Remittances and their Effect on Emigration Intentions in Egypt, Morocco and Turkey - Hendrik P. van Dalen; George Groenewold; Tineke Fokkema (Tinbergen Institute, 2005)
What determines remittances – altruism or enlightened self-interest - and do remittances trigger additional migration? These two questions are examined empirically in Egypt, Turkey and Morocco for households with family members living abroad. Results show, first, that one cannot clearly pinpoint altruistic or motives of self-interest since each country tells a different story and within a country both motives can be defended as driving forces behind remittance behaviour. A general conclusion based on a multi-country study is that the family ties and the net earnings potential of emigrants have stronger effects on receipt of remittances than net earnings potential of households in the country of origin. Second, the receipt of remittances has a positive effect on emigration intentions of household members living in the country of origin. Therefore, receipt of remittances may contribute to new flows of migration, in particular in the case of Morocco.
Keywords: D13; D85; F22; N37; O16; 330; Remittances; migration; intentions; altruism; self-interest; networks; Rücküberweisungen; Internationale Wanderung; Altruismus; Eigeninteresse; Schätzung; Ägypten; Marokko; Türkei